Revenue and Knowledge Cooperation Mechanisms between Business Incubators and Venture Capitalists for Collaborative Start-Ups - Wu, Wenqing; Han, Qing (Scientific Research, 2017)
Business incubators and venture capital are effective instruments for supporting the development of new firms. The purpose of this paper is to explore cooperation mechanisms between business incubators and venture capitalists and find the equilibriums of the mechanisms. Also, this paper puts forward three mechanisms, revenue sharing mechanism, cost sharing mechanism and knowledge sharing mechanism, to discuss the cooperation between business incubators and venture capitalists. Meanwhile, we consider the effect of the business incubator’s altruism and compare the three cooperation mechanisms with and without altruism. The results indicate that the mechanism of revenue sharing leads to the highest incubator’s revenue sharing proportion. Additionally, the incubator’s revenue sharing proportion decreases even though its final profit increases when considering altruism. Therefore, the nonprofit incubator can be better for cooperating with the venture capitalist than the profit incubator. Finally, financial returns can influence their cooperation.
Keywords: Business Incubator; Venture Capitalist; Revenue Sharing Mechanism; Cost Sharing Mechanism; Knowledge Sharing Mechanism